Modelos Estocásticos De Elección De Compra Recurrente Aplicados En Hogares De La Ciudad De México - Fischer, Laura; Espejo, Jorge (European Scientific Journal, ESJ, 2018)
This paper focuses on examining the behaviors of repeated purchase, brand duplication, shared loyalty, and double risk using stochastic models of recurring purchase decision. A quantitative study was carried out using the panel technique in 60 homes in Mexico City. Within a period of 12 weeks, the recurring purchasing behavior of these households was recorded and analyzed. The results show, in a scientific way, the behavior of recurrent purchases in Mexican households.